(untitled) (Iraqi National Journal of Earth Science (INJES), 2018)
c and hol>c are the most dominant joints in the first three traverses whereas hko>a system and ac set are abundant in the fourth traverse. It also revealed that the system hko>a are more abundance than hko>b system which indicate that the compression phase was tensive than the alternative tension. Faults were investigated by field work and satellite image interpretation. It revealed three strike-slip faults inclined to the fold axis. They are BF1, BF2 and Besary faults. Another fault was concluded from the geometric properties and vergency of Brifka anticline. It is a foreland listric fault. This was followed by the determination of the formation thicknesses in order to conclude the sense of displacement of this fault. The determination appeared that the thicker sediments are in the area of the southwestern limb reflecting that the fault is reactivated as reverse foreland listric fault.(.]]>